2022
DOI: 10.1101/2021.12.30.21268495
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comparison of outcomes from COVID infection in pediatric and adult patients before and after the emergence of Omicron

Abstract: Background The Omicron SARS-CoV-2 variant is rapidly spreading in the US since December 2021 and is more contagious than earlier variants. Currently, data on the severity of the disease caused by the Omicron variant compared with the Delta variant is limited. Here we compared 3-day risks of emergency department (ED) visit, hospitalization, intensive care unit (ICU) admission, and mechanical ventilation in patients who were first infected during a time period when the Omicron variant was emerging to those in pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
137
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(158 citation statements)
references
References 7 publications
20
137
0
1
Order By: Relevance
“…Reports of disease severity upon infections with SARS-CoV-2 Omicron, though at first anecdotal [38] or based on preliminary clinical studies [39][40][41], were validated by recent clinical studies from other parts of the world [42,43], confirming an overall less severe, rather mild, or even asymptomatic disease outcome, which again stands in agreement with results from in vitro studies [44] as well as with weaker binding of the virus to its receptor. Enhanced replication of SARS-CoV-2 Omicron in nasal epithelial cells has been shown and supports higher contagiousness whereas the reduced viral yields in human lung cells are in line with reduced disease severity [45].…”
Section: A Molecular Perspective On Transmissibility and Disease Outcomesupporting
confidence: 72%
“…Reports of disease severity upon infections with SARS-CoV-2 Omicron, though at first anecdotal [38] or based on preliminary clinical studies [39][40][41], were validated by recent clinical studies from other parts of the world [42,43], confirming an overall less severe, rather mild, or even asymptomatic disease outcome, which again stands in agreement with results from in vitro studies [44] as well as with weaker binding of the virus to its receptor. Enhanced replication of SARS-CoV-2 Omicron in nasal epithelial cells has been shown and supports higher contagiousness whereas the reduced viral yields in human lung cells are in line with reduced disease severity [45].…”
Section: A Molecular Perspective On Transmissibility and Disease Outcomesupporting
confidence: 72%
“…Several studies have found similar reductions in severity with infection from Omicron compared to infection from other SARS-CoV-2 variants. In other settings, estimated reductions in risk of hospitalization with Omicron variant infection have ranged from 20-80% [9][10][11]22,23]. Variability in estimates between studies is likely in part due to different definitions of the primary endpoint (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Although Omicron showed a greater ability to evade immunity developed by vaccinations and previous infections, we found signi cantly reduced severity in Omicron infections. Almost all the studies we reviewed consistently reported a considerably lower risk of requiring hospital admission, ICU, and mechanical ventilators, shorter median stay at the hospital, and lower mortality rates among Omicron infections compared to Delta and other variants [3], [9], [16]- [19]. Also, we found that though Omicron has a greater ability to escape immunity developed by vaccines, booster/third doses are still signi cantly effective in protecting from symptomatic Covid infections [16].…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective cohort study (Omicron cohort and Delta cohort) was carried out using electronic health record (EHR) data from 577,938 rst-time SARS-CoV-2 infection patients in the United States [19]. After adjustment for demographics, socioeconomic determinants of health, comorbidities, medications, and immunization status, the 3-day risks in the Emergent Omicron cohort were consistently less than half of those in the Delta cohort: Emergency Department (ED) visit: 4.55% vs. 15.22% (risk ratio or RR: 0.30, 95% CI: 0.28-0.33); hospitalization: 1.75% vs. 3.95% (RR: 0.44, 95% CI: 0.38-0.52]); ICU admission: 0.26% vs. 0.78% (RR: 0.33, 95% CI:0.23-0.48); mechanical ventilation: 0.07% vs. 0.43% (RR: 0.16, 95% CI: 0.08-0.32) [19].…”
Section: Severitymentioning
confidence: 99%